PENGARUH PERSEPSI KEMUDAHAN PENGGUNAAN DAN PERSEPSI KEAMANAN TRANSAKSI TERHADAP MINAT MENGGUNAKAN APLIKASI DANA PADA MAHASISWA FAKULTAS EKONOMI UNIVERSITAS NEGERI JAKARTA - Prianda Saputra; Muhammad Rafli, Batahan Renaldi, Shuja Azmi Ismail, Hendryawan Cipta Mulia (Jurnal Ekonomi dan Bisnis, 2025)
This aims to analyze the influence of perceived ease of use and perceived security on the interest in using the DANA application among students of the Faculty of Economics, Universitas Negeri Jakarta. The rise of financial technology usage has significantly changed the landscape of financial services, particularly in the context of digital payment systems like e-wallets. DANA, a leading digital wallet launched on November 5, 2018, has gained popularity, especially among millennials who prioritize convenience and security in their transactions.Using a quantitative approach with a survey method, data were collected from 100 respondents through a structured questionnaire. The data were analyzed using Structural Equation Modeling (SEM) with Partial Least Squares (PLS). The findings reveal that both perceived ease of use and perceived security have a positive and significant effect on students' intention to use the DANA application. Specifically, as users perceive the application to be easier and more secure, their interest in utilizing DANA for daily transactions increases.